Self care interventions could advance sexual and reproductive health in humanitarian settings - Logie, Carmen H; Khoshnood, Kaveh; Okumu, Moses; Rashid, Sabina Faiz; Senova, Fidan; Meghari, Hamza; Kipenda, Claire Uwase (BMJ (Online), 2022)
This article was published in the BMJ Open [Copyright © 2019, BMJ Publishing Group Ltd] and the definite version is available at: https://doi.org/10.1136/bmj.l1083 The Journal's website is at: https://www.bmj.com/content/365/bmj.l1083